Study on the origin and nature of the adenomatoid odontogenic tumor by immunohistochemistry - Crivelini, Marcelo Macedo [UNESP] (2005)
The adenomatoid odontogenic tumor (AOT) is a clinically benign lesion. Discussions about the AOT hamartomatous or neoplastic nature, and the probable odontogenic epithelial cell it originates from still exist. This research aimed to study and discuss the subject by the immunohistochemical detection of cytokeratins, laminin, collagen IV, PCNA and p53 in 8 tumor samples and 8 dental follicle samples containing reduced enamel epithelium. The results have shown that CK14 labelling indicated differentiation grades for secreting ameloblasts or ameloblasts in the post-secreting stage in the adenomatoid structure of AOT. Laminin, found on the luminal surface of adenomatoid structures, was compatible with the reduced enamel epithelium during the protective stage of amelogenesis. PCNA specifically labelled the spindled areas and peripheral cords of the AOT, indicating that these areas are responsible for tumor growth. After considerations about pathogenesis, the authors suggested that the nature of AOT is hamartomatous with histogenesis from the reduced enamel epithelium.